2022
DOI: 10.1371/journal.pone.0270768
|View full text |Cite
|
Sign up to set email alerts
|

The level and determinants of COVID-19 vaccine acceptance in Ghana

Abstract: Objective As part of the efforts to curb the COVID-19 pandemic, the government of Ghana has received several shipments of approved vaccines, and administration has begun in the country. Studies examining the determinants of COVID-19 vaccine acceptance in Ghana were mostly conducted before the vaccination exercise. Vaccine acceptance decisions however vary with time and hence, peoples’ decisions may have changed once vaccines became accessible. This study examines the level and determinants of COVID-19 vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 87 publications
1
13
1
1
Order By: Relevance
“…Furthermore, religious influence in vaccination has been observed since Christians have a higher likelihood of taking the vaccine, which is in congruence with a review of 12 Sub-Saharan African countries, including Ghana, which also stated that vaccine hesitancy has been due to religious beliefs, which could be overcome through communication strategies by addressing the concerns of the community [ 31 ]. We observed that there were higher odds of taking the first shot of the vaccine among participants with three years of experience, which is consistent with the findings of a study that reported that occupation influenced the acceptance of the COVID-19 vaccine in Ghana [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, religious influence in vaccination has been observed since Christians have a higher likelihood of taking the vaccine, which is in congruence with a review of 12 Sub-Saharan African countries, including Ghana, which also stated that vaccine hesitancy has been due to religious beliefs, which could be overcome through communication strategies by addressing the concerns of the community [ 31 ]. We observed that there were higher odds of taking the first shot of the vaccine among participants with three years of experience, which is consistent with the findings of a study that reported that occupation influenced the acceptance of the COVID-19 vaccine in Ghana [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the findings revealed the ambivalence of persons with disabilities toward vaccination, probably indicating that those who participated in this study were neither positive nor negative toward receiving the vaccination. This finding is different from studies conducted in Ghana which reported that persons without disabilities had positive attitudes toward COVID-19 vaccination (Kishore et al 2021; Kyei-Arthur et al 2022; Okai and Abekah-Nkrumah 2022). This finding was different from studies conducted elsewhere which reported a high likelihood that the general population would have a COVID-19 vaccination (Al-Kafarna et al 2022; Al-Mohaithef and Padhi 2020; Edwards et al 2021; Kalam et al 2021; Khubchandani et al 2021; Schwarzinger et al 2021; Yasmin et al 2021) or hesitancy (Ahmed Khidir 2021; Cooper, van Rooyen, and Wiysonge 2021) towards the vaccination.…”
Section: Discussioncontrasting
confidence: 99%
“…Kết quả nghiên cứu của chúng tôi phù hợp với tỷ lệ chấp nhận tiêm chủng chung của các nước. Nghiên cứu của Grace Adjei Okai, 62,7% người nghiên cứu chấp nhận tiêm ngừa vaccine nếu như được cung cấp miễn phí trong vòng 12 tháng tới [10]. Sự khác biệt về tỷ lệ bao phủ vaccine giữa các quốc gia có thể làm trì hoãn việc kiểm soát đại dịch mức độ từng quốc gia đến cả toàn cầu và tốc độ hồi phục kinh tế, xã hội sau đại dịch.…”
Section: Bàn Luậnunclassified